Adaptation and Valorization of Entrepreneurship in Irrigated Agriculture (AVENIR) baseline study - Muriithi, Cyrus K; Mwongera, Caroline; Abera, Wuletawu; Nyakundi, Fridah Nyabate; Chege, Christine G. Kiria; Nguru, Wilson (2021)
The objective of the baseline study was to evaluate conditions in the Sedhiou and Tambacounda Regions of Senegal for the AVENIR project. The study entailed observation of key trends, a household survey, and analysis of the biophysical characteristics of the project area and challenges for agriculture. Thereby, the study identified key lessons learned and documented challenges for agriculture development.